Identifikasi Faktor-Faktor yang Mempengaruhi Kecepatan Arus Laut di Perairan Selat Sunda - Anton Daud; Danar Guruh Pratomo; Khomsin; Agie Wandala Putra (Lembaga Bale Literasi, 2025)
The Sunda Strait is a strategically body of water that connects the Indian Ocean with the Java Sea.. Besides being a busy international shipping route, it also exhibits complex oceanographic characteristics, particularly in relation to ocean current dynamics. Ocean currents in this region play a key role in sediment distribution, and the safety and efficiency of maritime navigation. This study aims to identify and analyze the factors influencing ocean current speed in the Sunda Strait using a literature study method. Data were collected from scientific journals, reference books, and relevant previous research reports. A qualitative descriptive analysis was conducted to interpret findings from various sources. The study reveals that the speed of ocean currents in the Sunda Strait is affected by a combination of oceanographic and meteorological factors. Key influences include seabed topography, depth variations, sea surface temperature, seasonal wind patterns, tidal dynamics. Narrow passages and uneven seabed contours can either accelerate or slow down water flow in different locations. Sea surface temperature differences and monsoonal wind patterns, influence both the direction and strength of water mass movements. Furthermore, tidal dynamics contribute to periodic changes in current speed and direction, helping to shape circulation patterns throughout the strait. Understanding the interaction of these multiple factors is essential for effective coastal resource management, navigation safety, and marine risk mitigation. This study recommends further research involving in-situ field observations and the application of numerical modeling to provide a more detailed and accurate analysis of ocean current dynamics in the Sunda Strait